Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
(a-b)^2 = a^2-2ab+b^2
(8-5i)^2 = 8^2-2(8)(5i)+(5i)^2
= 64-80i+25i^2
i^2=-1
So
= 64-80i+25(-1)
=64-25-80i
= 39 - 80i
which is your answer :)
(8-5i)^2 = 8^2-2(8)(5i)+(5i)^2
= 64-80i+25i^2
i^2=-1
So
= 64-80i+25(-1)
=64-25-80i
= 39 - 80i
which is your answer :)
(8 - 5i)²
(8 - 5i)(8 - 5i)
64 - 40i - 40i + 25i²
64 - 80i + 25i²
64 - 80i + 25(-1)
64 - 25 - 80i
39 - 80i
(8 - 5i)(8 - 5i)
64 - 40i - 40i + 25i²
64 - 80i + 25i²
64 - 80i + 25(-1)
64 - 25 - 80i
39 - 80i
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.